A szociálisprobléma-megoldó és az induktív gondolkodás kapcsolata 8, 12, 15 és 18 évesek körében - Kasik, László (Magyar Pedagógia, 2012)
The aim of this cross-sectional study was to examine the relationship between social problem solving and inductive reasoning among 8- to 18-year-old students (N=737) in a Hungarian context. The SPSI–R:S questionnaire of social problem solving was adapted (D’Zurilla, Nezu and Maydeu-Olivares, 2002) and targeted the following SPS factors: positive and negative problem orientation, rationality, impulsivity, and avoidance. The characteristics of inductive reasoning (number analogies, verbal analogies, and number series) were examined with the Inductive Reasoning Test (Csapó, 1998) and the author’s questionnaire was administered for information on family background. Both questionnaires had good reliability (Cronbach-α values are above .88). In addition to children’s own evaluations, mothers and teachers also evaluated the functioning of SPS (using the same questionnaire). The results suggest significant differences between the younger (8- and 12-year olds) and the older students (15- and 18-year-olds) in the case of positive orientation, rationality and impulsivity (with the younger students having higher values). However, the values of negative orientation and avoidance show intensifying tendencies with age (the oldest students have the highest values). For all factors, children’s and mothers’ ratings of children’s SPS show more similarity than children’s and teachers’ ratings or teachers’ and mothers’ ratings. Regression analyses for SPS factors reveal that the three areas of inductive reasoning explain smaller proportions of variances than the social factors. The relationships between verbal analogies and positive orientation, and between verbal analogies and rationality are the strongest, whereas the number series have the smallest effects on the SPS factors. As regards family characteristics, the effects of parental educational levels are moderate in all age groups. The effects of mothers and fathers are different on SPS factors. Maternal influence is more pronounced on avoidance, impulsivity and negative orientation. On the other hand, fathers have a more considerable effect on positive orientation and rationality.